ASME 2020 Internal Combustion Engine Division Fall Technical Conference 2020
DOI: 10.1115/icef2020-2911
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of NOx Emissions for a Range of Engine Hardware Configurations Using Artificial Neural Networks

Abstract: The predictive ability of artificial neural networks where a large number of experimental data are available, has been studied extensively. Studies have shown that ANN models are capable of accurately predicting NOx emissions from engines under various operating conditions and different fuel types when trained well. One of the major advantages of an ANN model is its ability to relearn when new experimental data is available, thus continuously improving its accuracy. The present work explored the potential of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Moreover, Papaiouannou [27] proposes a Random Forest algorithm to predict particulate emissions in a GDI engine. It is a simple model, easier to understand and less computationally expensive than deep neural networks.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Papaiouannou [27] proposes a Random Forest algorithm to predict particulate emissions in a GDI engine. It is a simple model, easier to understand and less computationally expensive than deep neural networks.…”
Section: Introductionmentioning
confidence: 99%
“…Desantes et al as early as 2002, predicted NOx and soot from a Euro IV heavy duty diesel engine [20], showing strong correlations. Subsequent studies from different diesel engines of all sizes have shown that ANNs can be used predictively, particularly for NOx emissions [18,[21][22][23][24][25]. Studies using ML techniques for the prediction of emissions formation from gasoline engines, particularly GDI engines are sparse in the literature, and the authors are not aware of any studies which predict PM or PN emissions from GDI engines using ML techniques in the literature.…”
Section: Introductionmentioning
confidence: 99%